Disiplin Pengelolaan Keuangan (Survei Umkm Di Provinsi Gorontalo) - Muhammad Anas; Ariawan Ariawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Financial management discipline is a central issue in the field of microfinance studies. The purpose of this study is to investigate and analyze the influence of the role of government, employers competencies, financial administration practice,and financial commitment on financial disciplineof SMEs in the province of Gorontalo either partially or simultaneously. This study was conducted using the survey design to obtain information on issues related to the study variables. Respondents were used as a sample is 200 people with the criteria are the bussinesalready exist at least two years, at aleast has one employee andhas permanent location. The analytical tool used is multiple regression analysis. The results showed that the role of government, employers competencies and financial commitments have a significant impact on the financial discipline of SMEs in the province of Gorontalo. Meanwhile, the practice of financial administration has no significant effect on the financial discipline of SMEs in the province of Gorontalo. This study also shows that SMEs still have a low awareness about how to learn good financial discipline. On the other hand, SMEs have a high financial commitment to expand its business. The role of government is needed to improve the financial discipline SMEs in managing their business.